(untitled) (Research, Society and Development, 2020)
This work aims to report the experience of Nursing students in a supervised internship field, during the provision of intensive neonatal care, as well as the interventions developed in order to improve the quality of care in the sector. This is an experience report lived by students of the Bachelor of Nursing course, during the Curricular Stage II discipline, which had a Neonatal Intensive Care Unit as its setting. Situational analysis of the unit was performed; then a planning of the interventions was constructed and, finally, their implementation during the internship period. The field of practice provided the development of knowledge, skills and abilities of the students in the field of neonatology. The activities developed by the academics promoted greater organization and agility in assisting the newborn; improved reception of parents and relatives of newborns admitted to the NICU; implementation of a routine for evaluating and controlling the quality of care provided in the sector and creating a space for the exchange of knowledge and practices among the entire health team. From the work, it is clear that the existence of students in the health unit can act as an incentive to the reflective practice of the service professionals.